Multiple pilomatricomas associated with partial trisomy 9. A case report. - Albornoz-Serqueira, R.; Minuzzi, G.; Truffello-Tobar, D.; Pereira-Rudolph, F.; Rojas-Muñoz, F.; Macías-Eslava, M.A. (European Journal of Pediatric Dermatology, 2020)
Pilomatricoma is a benign neoplasm of the hair matrix cells, common in pediatric age, usually presenting on the head or upper trunk. Pilomatricomas in their multiple form are uncommon, and when they do occur, they are generally associated with a syndrome. We present a 12-year-old girl with partial trisomy 9, associated with multiple pilomatricomas.